(untitled) (Revista do Centro de Estudos Portugueses, 2000)
A questão indígena na obra do Padre Antonio Vieira é constantemente abordada, principalmente por estudiosos brasileiros. Apesar de alguns autores levarem em consideração as questões políticas que envolvem a atuação missionária do jesuíta, poucos consideram sua postura frente a restauração portuguesa. O presente artigo tem por objetivo demonstrar, de modo sucinto, como Vieira entendia a questão indígena à luz de suas preocupações com o reino, aliadas às suas expectativas messiânicas. The indigenous matter in Priest Antônio Vieira’s work is constantly approached, mainly for Brazilian specialists. In spite of some authors take account of the political matters that involve the jesuit’s missionary performance, a few of them consider his posture over the Portuguese Restoration. The present article has the purpose of demonstrating, in a brief way, how Vieira understood the indigenous matter in the light of his concerns about the new dynasty, allied to his messianic expectations.